Pendidikan Akal dalam Perspektif Al-Qur’an (Analisis Al-Qur’an Surat Ali Imran Ayat 190-191) - Rizky PajarPerdana (Fakultas Pendidikan IAI Pangeran Dharma Indramayu, 2026)
This research aims to find out the meaning of reason in an Islamic perspective and analyze the concept of reason education in the perspective of the Al-Qur'an Surah Ali Imran verses 190-191. This research is a descriptive qualitative research study of libraries (library research), by collecting data from various related sources and then analyzing it to draw conclusions. Research studies show that the meaning of reason in the Islamic perspective is a tool used for the thinking process. In this context of thinking, reason has a very important role, because it is able to achieve understanding, knowledge and awareness through stages that are scientific, empirical and philosophical. All of these processes are carried out on the basis of the Al-Qur'an and hadith, with the aim of advancing human life in this world. Meanwhile, the concept of intellectual education in the Al-Qur'an, Ali Imran verses 190-191, emphasizes the importance of using reason to reflect on and understand the signs of the greatness of Allah SWT. which is clearly seen in His creation. In this verse, Allah SWT. calls on people who have reason to observe the universe and the changes that occur in it as proof of His existence and power, both in terms of metaphysics, cosmology, ethics and aesthetics using the tafakkur and tazakkur methods. So that through this concept, perfect reason can be realized according to Islamic teachings.